Tank mixture of propanil and quinclorac for inhibiting a bispyribac-sodium-resistant barnyardgrass (Echinochloa crus-galli) biotype in Malaysia - Gobi, Kashturi; Ahmad-Hamdani, Muhammad Saiful; Zakaria, Norazua; Dilipkumar, Masilamany; Chuah, Tse-Seng (Advances in Weed Science, 2025)
Background Herbicide-resistant E. crus-galli poses a significant threat to rice production in direct-seeded rice systems.Objective This study aimed to confirm the presence of bispyribac-sodium-resistant (R) E. crus-galli and determine the optimal mixture ratio of propanil and quinclorac to control the R biotype.Methods E. crus-galli seeds from putative resistant and susceptible biotypes were collected from rice fields located 10 km apart in Alor Setar, Kedah, Malaysia, and screened with bispyribac-sodium, propanil, and quinclorac. Dose-response tests were conducted to confirm herbicide resistance. Propanil and quinclorac were tank-mixed at ratios of 20:80, 40:60, 60:40, and 80:20 and their inhibitory effects were evaluated under glasshouse conditions.Results Dose-response tests showed a 128-fold increase in the resistant biotype (R) compared to the susceptible (S) biotype based on the dosage corresponding to 50% inhibition of shoot growth, and a 70-fold increase based on the dosage that caused 50% mortality. The mixture ratios of propanil and quinclorac exhibited synergistic action except for the 80:20 ratio, which was antagonistic. The 40:60 mixture ratio outperformed the others, allowing the rates of propanil and quinclorac to be reduced by 2.2 and 4.7-fold, respectively, compared to their single applications to achieve 95% mortality. Conclusions: Dose-response tests revealed a high resistance level in the R biotype to bispyribac-sodium. Propanil and quinclorac at recommended rates were effective in controlling the R biotype. This study demonstrates that the ratio of propanil in combination with quinclorac is crucial in enhancing the herbicidal activity.